Memory before modernity : practices of memory in early modern Europe - Kuijpers, Erika; Pollmann, Judith; Müller, Johannes; Steen, Jasper van der (2013)
This volume examines the practice of memory in early modern Europe, showing that this was already a multimedia affair with many political uses, and affecting people at all levels of society; many pre-modern memory practices persist until today.